Anomalies of electroconductivity and intraplate earthquakes of the western part of the Ukrainian Shield and Volyno-Podolian Plate - A. N. Kushnir; T.K. Burakhovich (Геофизический журнал, 2012)
Threedimensional geoelectric model of the Earth’s crust and upper mantle of the MogilevPodolNovodnestrovian seismically dangerous area is characterized by electroconducting zones at the depths from 3 to 5 km with ρ=10 Om·m, from 15 to 30 km with ρ=30 Оm·m and from 50-70 to 120 km with ρ=30 Оm·m. On the base of the results of geoelectric studies, characteristics of MogilevPodolNovodnestrovian seismically dangerous zone which is confined to joint areas of Podolian, Belotserkovian, Zhmerynskiy and other ones of deep faults with lower range have been replenished and specified.